Otomasi Pengaturan Suhu Water Heater Menggunakan Mikrokontroller dengan Media Paraffin Wax - Elsa Maulinda Savana; Henna Nurdiansari; Vigih Hery Kristanto (Pusat riset dan Inovasi Nasional, 2025)
Water heating systems on ships play a crucial role in supporting crew comfort and operations. However, conventional systems generally operate continuously without automatic control, resulting in energy waste and high operational costs. This situation drives the need for innovation in more efficient and environmentally friendly water heater designs. This research aims to design and implement an automated water heater temperature control system based on an ESP32 microcontroller with on/off control and the use of paraffin wax as a latent heat storage medium. This design is expected to improve energy efficiency while reducing the operational costs of water heaters on ships. The research methodology includes system design, hardware assembly, and performance testing, both static and dynamic. Testing was conducted to evaluate temperature stability and energy efficiency in system conditions with and without the use of paraffin wax. The results showed that paraffin wax improved water temperature stability while reducing the frequency of heater activation. In a 24-hour test, the system without paraffin wax recorded a heater operating time of 15 hours, consuming 8.85 kWh of electricity and costing Rp11,965.20. In contrast, the Paraffin Wax system only requires 10 hours of heater operation, consumes 5.90 kWh, and costs Rp7,976.80. This demonstrates energy savings of 2.95 kWh and a cost efficiency of up to 58%. Therefore, the ESP32-based water heater automation system and heat storage using Paraffin Wax are proven to be more energy-efficient, cost-effective, and have the potential to be an innovative and environmentally friendly solution for ship operational needs.